Antibiotic Disk Susceptibility Tests with Neisseria gonorrhoeae - Maier, Thomas W. (1974)
We have used a standardized disk diffusion procedure to test the susceptibility of 892 isolates of Neisseria gonorrhoeae to six antibiotics. The disk diffusion test described is a modification of the disk test of Bauer, Kirby, Sherris, and Turck, which is widely used for susceptibility testing of fast-growing, aerobic pathogens. With all six antibiotics (penicillin, ampicillin, tetracycline, erythromycin, chloramphenicol, and cephaloridine), disk test results were found to be reproducible and correlated well with the minimal inhibitory concentration as determined by an agar dilution procedure. The coefficients of correlation ranged from −0.79 with cephaloridine to −0.93 with penicillin. The technique described for disk susceptibility testing of gonococci can be used both for research and clinical purposes.